The impact of natural resource dependence and green finance on green economic growth in the context of COP26. (March 2023) - Tan, Junlan; Su, Xiang; Wang, Rong
Abstract: The cop26 conference proposed that in order to cope with climate change, global countries need to focus on green economic growth (GEG) and accelerate green transformation. This paper adopts panel data of 30 provinces in China from 2008 to 2021 to measure the level of regional GEG, incorporating natural resource dependence, green finance and regional GEG into an overall research framework, and using a systematic GMM model to explore the relationship of them, and concludes as follows: (1) In the temporal dimension, GEG in China has increased, and each province generally shows a "U" shape development trend. From the spatial dimension, the overall change trend of each region shows that the GEG of each region in China shows an upward trend, with the western region increasing more and the eastern region increasing the least. (2) The phenomenon of "resource curse" exists in the eastern, western regions and the whole country, while insignificant in the central region, which does not reflect the "resource curse effect". Green finance has a significant positive effect on the GEG of all the regions, with the most significant effect value in west, followed by Central and the weakest in East. (3) The per capita GDP of all regions can improve GEG. Environmental regulation promotes GEG at the national level and in the east, with a non-significant effect test in central and a negative in western region. Human capital level promotes GEG in all regions; foreign direct investment promotes GEG in all regions. The work can provide reference for achieving regional green economic transformation. Highlights: Study green economic growth in the context of COP26. Measure green economic growth using the super-SBM model. Use the system GMM to verify the influencing factors of green economic growth. Make recommendations to improve green economic growth.